Correspondence: Probiotic (Lactobacillus reuteri Protectis) in premature infants - Authors' reply - Marjana Jerković Raguž; Jerko Brzica; Sanja Rozić; Darinka Šumanović Glamuzina; Antonija Mustapić; Marija Novaković Bošnjak; Tomica Božić (Hygeia Press di Corridori Marinella, 2017)
Dear Editor, We thank the authors for their interest and comments on our paper. They have raised some very valid points. This corrispondence refers to the following article: Jerković Raguž M, Brzica J, Rozić S, Šumanović Glamuzina D, Mustapić A, Novaković Bošnjak M, Božić T. The impact of probiotics (Lactobacillus reuteri Protectis) on the treatment, course and outcome of premature infants in the Intensive Care Unit in Mostar. J Pediatr Neonat Individual Med. 2016;5(2):e050228. doi: 10.7363/050228. Comments can be found in the following article: Mandal A, Sahi PK. Correspondence: Probiotic (Lactobacillus reuteri Protectis) in premature infants. J Pediatr Neonat Individual Med. 2017;6(1):e060129. doi: 10.7363/060129.